Maximal aerobic capacity in ageing subjects: actual measurements versus predicted values. Issue 1 (17th March 2016) - Pistea, Cristina; Lonsdorfer, Evelyne; Doutreleau, Stéphane; Oswald, Monique; Enache, Irina; Charloux, Anne
We evaluated the impact of selection of reference values on the categorisation of measured maximal oxygen consumption ( V ′O2 peak ) as "normal" or "abnormal" in an ageing population. We compared measured V ′O2 peak with predicted values and the lower limit of normal (LLN) calculated with five equations. 99 (58 males and 41 females) disease-free subjects aged ≥70 years completed an incremental maximal exercise test on a cycle ergometer. Mean V ′O2 peak was 1.88 L·min −1 in men and 1.26 L·min −1 in women. V ′O2 peak ranged from 89% to 108% of predicted in men, and from 88% to 164% of predicted in women, depending on the reference equation used. The proportion of subjects below the LLN ranged from 5% to 14% in men and 0–22% in women, depending on the reference equation. The LLN was lacking in one study, and was unsuitable for women in another. Most LLNs ranged between 53% and 73% of predicted. Therefore, choosing an 80% cut-off leads to overestimation of the proportion of "abnormal" subjects. To conclude, the proportion of subjects aged ≥70 years with a "low" V ′O2 peak differs markedly according to the chosen reference equations. In clinical practice, it is still relevant to test a sample of healthy volunteers and select the reference equations that better characterise this sample. As V ′ O 2 peak % pred differs markedly with the reference value, reference equation choice is critical in the elderly http://ow.ly/YsXHD